Programmable material testing device for mechanoluminescence measurements. (October 2022) - Einbergs, Ernests; Zolotarjovs, Aleksejs
Graphical abstract: Abstract: Mechanoluminescent materials transform mechanical energy into visible light. Phenomena could prove to be advantageous to various next-generation monitoring systems employed in the fields of security and healthcare if the intrinsic mechanisms are fully understood. Scientific efforts are mainly hindered by the lack of equipment capable of controlled mechanical deformation and simultaneous collection of light emitted by the sample. This article describes an easily constructible material testing device (508 €) with an interchangeable test fixture and an integrated load cell made from readily available mechanical components and 3D printed parts. A commercial low-cost alternative to spectroscopic apparatus (200 €) has recently become available alongside a highly capable 16-bit CMOS camera intended for low light conditions (520 €). A highly modular prototype system with an overall cost much lower than commercial alternatives that provide less functionality could enable a larger portion of scientific personnel to contribute to a novel field of research.